1993
DOI: 10.1080/00018739300101494
|View full text |Cite
|
Sign up to set email alerts
|

The superconducting mixed state of artificial microstructures

Abstract: The use of ordered microstructures makes it possible, on the one hand, to obtain new (including quantitative) information on elementary pinning forces and on methods of their summation and, on the other hand, to observe interesting effects based on the coherent behaviour of Abrikosov vortices in them. Some progress in these fields of research, has been achieved at the present time. We believe that today the study of quasiperiodic structures and, in particular, pinning in these structures, is also a topical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 104 publications
2
25
0
Order By: Relevance
“…In our analysis the surface superconductivity 18 is ignored as well as the possibility of kinks in the vortex structure. 1,19 The agreement of our theoretical results with the H p (T) behavior observed in Nb/Pd multilayers 16 is quite good.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…In our analysis the surface superconductivity 18 is ignored as well as the possibility of kinks in the vortex structure. 1,19 The agreement of our theoretical results with the H p (T) behavior observed in Nb/Pd multilayers 16 is quite good.…”
supporting
confidence: 80%
“…1 In particular, superconductor/normal-metal ͑S/N͒ multilayers have attracted great attention because they allow to investigate the influence of the reduced dimensionality on different physical properties and to obtain more information on analogous effects observed in high-temperature superconductors. The properties of S/N multilayers in the region of the superconducting transition temperature T c were firstly described by de Gennes.…”
mentioning
confidence: 99%
“…The interaction between the vortices and the defects influences the absolute value of J c , its magnetic field dependence and the pinning force F p (H ) = |J c × H| [8]. When the period of the vortex lattice is almost equal to the period of inhomogeneities, the vortex mobility can be lowered and the J c values grow at a certain magnetic field (the so-called peak effect [9]). Moreover, if the microstructure of the superconducting film is columnar, peculiar properties of J c ( ) are observed ( is the angle between the magnetic field and the film surface): for instance, the way in which J c approaches = π/2 and the fact that the maximum of J c is observed at is slightly different from zero [4,5,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In this case the vortices center of mass (CM) move with velocity V d = F d /η and in the CM frame of reference, defined by r ′ l = r l − V d t, the equations of motion are as in Eqs. (1), but without the driving term F d and with the vortex-CDL force replaced by the time-dependent interaction F (t) for which Q · V d = 0 oscillate fast, thus having a negligible effect on the vortex trajectory [11]. The vortex-CDL force in the CM frame reduces then to the static one obtained by summing the Fourier components in F…”
mentioning
confidence: 99%
“…Understanding the dynamical phases in this case is of interest because it may be possible to observe them in superconducting films with periodic arrays of holes, magnetic dots and columnar defects (CD). Several techniques have been developed to fabricated these films and studies of vortex dynamics in them have been reported [1,2]. Theoretical workers have carried out investigations, mostly numerical, of driven vortices under periodic pinning [3][4][5][6].…”
mentioning
confidence: 99%